Binder-free 3D flower-like alkali doped- SnS2 electrodes for high-performance supercapacitors. (20th April 2021) - Setayeshmehr, Mahboobeh; Haghighi, Maryam; Mirabbaszadeh, Kavoos
Highlights: The presence of the alkali metals (Li, Na, K, Cs) with SnS2 flower-like nanostructure improved its electrochemical activity through increasing of d-spacing and electrical conductivity of SnS2 . Presence of the alkali metals (Li, Na, K, Cs) led to the great increasing of SnS2 d-spacing, and thus an improvement in the SnS2 intercalation of electrolyte ions. Among the alkali metals (Li, Na, K, Cs), the Na metal leads to a higher conductivity of SnS2 than other elements, resulting in a higher current density at a constant voltage and ultimately a better specific capacitance. Abstract: Tin disulfide can be a good electrode material in supercapacitors due to the presence of significant interlayer space in crystalline structures and large surface area. However, there are only a few reports of its supercapacitor applications. In this study, we report flower-like pure SnS2  and alkali metals (Li, Na, K and Cs) doped-SnS2  nanostructures synthetized by simple single-step solvothermal method without use of any surfactants. Results show that due to the presence of dopants, with increasing radius of the dopant element, the interlayer distance and dislocation intensity increase. This leads to an increase in the expanded space between interlayer and electro-active sites, and therefore, it is possible to intercalate more ions from the electrolyte. But due to the higher conductivity of Na than the other alkali metals, Na doped-SnS2  shows higher current density at constant voltage and thus better capacitance performance than the others. Na doped-SnS2  exhibits higher supercapacitor performance with a high capacitance of 269 Fg −1  at a current density of 1 Ag −1 . The significant electrochemical performance of Na doped-SnS2  can be attributed to its particularly good surface area due to the expansion of interlayer space, increasing of electro-active sites and greater conductivity due to the presence of Na. Graphical abstract: We prepare the pure and alkali metals-doped SnS2 flower-like nanostructures and demonstrate their electrochemical application as supercapacitor electrodes. Image, graphical abstract